The Implementation Of Convention On International Trade In Endangered Species Of Wild Fauna And Flora 1973 In Protection Orangutan In Aceh - Indah Fuji Lestari; Nellyana Roesa (Fakultas Hukum Universitas Syiah Kuala, 2018)
Orangutan is listed in Appendix I of The Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) 1973 as critically endangered species. Indonesia has ratified CITES under Precidential Decree No. 43 Year 1978 on the ratification of the CITES. Orangutan in Aceh has an extremely high risk of extinction caused by trade, fragmentation, possession and poaching. The aims of this study are to describe the implementation of CITES in Indonesia to protect Orangutan, to examine the obstacles faced by Aceh government and the efforts by Aceh government to protect Orangutan. This research is conducted through juridical empiric method. The data was obtained by conducting library research to acquire secondary data which sources include; legislations, books, online documents and other scholarly works and conducting field research, interviewing on respondents and informants as the primary data. Indonesia has adopted stricter domestic legislation under the Act No. 5 Year 1990 on the Biodiversity Conservation and Its Ecosystems, it was enacted the prohibitions and criminal sanction on the perpetrator who conducted illegal activities on wild fauna and flora. Indonesia also provide Government Regulation and several Ministerial Decree which contain spesific regulations, policies and procedures. The research found that one of the biggest problems is the law enforcement is not applied on the element of ownership of Orangutan which stated in the article 21 (2) of the Act No. 5 Year 1990. There are several obstacles in protecting Orangutan such as the lack of human resources, the lack of financial support, law enforcement, and the efforts by the government of Aceh are the enactment of Qanun No. 7 year 2016 on the Aceh Forestry, socialization about Orangutan as protected species, monitoring the Orangutan’s habitat, the confiscation on ownership of Orangutan and the establishment an Orangutan reintroduction center in Jantho. The recommendation are the government should revise the Act No. 5 year 1990 and the appendix Government Regulation No. 7 year 1999 to optimalize legal protection on Orangutan by increasing the punishment on the trade of Orangutan. The ownership of Orangutan must to be execute by the law and The Government of Aceh should be focus on the conservation effort of Orangutan.